The Relationship Between Organizational Culture and Project Performance - Ida Rizyani, Tahir; Mazita, Mokhtar; Azizan, Azit; Wan Khairul Anuar, Wan Abdul Manan; Airin, AbdulGhani; Wan Mohd Hafis, Wan Embong (2016)
This study is about the role organizational culture in project performance in construction industry, Pahang. It comes out based on the problem statement which project management sector is much rely on technological software instead of practicing organizational culture. The aim for this study is to identify the relationship between organizational culture and project performance and to determine the best practice of organizational culture dimension in a construction company in Pahang. The scope of this study is among employees and human resource manager at construction industry in Pahang especially in Kuantan. The total sample was 58 respondents from construction companies. The quantitative method was used. For the result of this study has been identified that there is significant relationship between organizational culture and project performance. The best practice of organizational culture is market culture and clan culture.